From Post to Exshaust : Kontribusi Self-Disclosure Terhadap Social Media Fatigue Pada Mahasiswa Universitas Negeri Padang - Alfanissa, Nur Fhadilla; Santoso, Indriyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is quantitative with a causal design. The population in this study consisted of students from Padang State University, with a sample of 109 respondents. Data analysis was conducted using assumption tests and simple linear regression with the help of SPSS for Windows. The results show that the level of self-disclosure among Universitas Negeri Padang students is mostly in the moderate category, with all aspects of self-disclosure also falling into the moderate category. The findings also indicate that the level of social media fatigue among students is moderate, which suggests that students are quite active in self-disclosure but are also beginning to experience social media fatigue. The hypothesis test results show a significant positive contribution of self-disclosure to social media fatigue with a significance value of (p < 0.05) and an R-square value of 0.227. This means that self-disclosure contributes 22.7% to social media fatigue, while the remaining percentage is explained by other factors outside this study.